2021
DOI: 10.3389/fphar.2020.596183
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Expenditures and Out-Of-Pocket Expenses in Patients With Stroke in Northeast China, 2015–2017: A Pooled Cross-Sectional Study

Abstract: Background: Stroke is the second most common cause of mortality worldwide and the leading cause of death in China. It imposes a heavy financial burden on patients, especially for some social groups that are vulnerable to economic risks.Objective: This study aimed to comprehensively assess the magnitude of hospital and out-of-pocket (OOP) costs associated with stroke in Northeast China.Methods: Patients were selected via a multistage stratified cluster random sampling approach. We reviewed all patients’ records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
10
3
Order By: Relevance
“…Different from previous studies [ 32 34 ], inpatient cost had no difference between ischemic and hemorrhage stroke in our study. This may be because conservative medical treatment without surgery in our neurology department.…”
Section: Discussioncontrasting
confidence: 99%
“…Different from previous studies [ 32 34 ], inpatient cost had no difference between ischemic and hemorrhage stroke in our study. This may be because conservative medical treatment without surgery in our neurology department.…”
Section: Discussioncontrasting
confidence: 99%
“…Different from previous studies [31][32][33] , inpatient cost had no difference between ischemic and hemorrhage stroke in our study. This may be because conservative medical treatment without surgery in our neurology department.…”
Section: Discussioncontrasting
confidence: 99%
“…After implementing ZMDP, the proportion of OOP in stroke patients in Shanxi Province decreased from 36.71% to 23.53%. Both are lower than previously reported in northeast China [ 35 ]. We found that the ZMDP had different effects on different subgroups.…”
Section: Discussioncontrasting
confidence: 71%